2015
DOI: 10.1515/nuka-2015-0030
|View full text |Cite
|
Sign up to set email alerts
|

Iron-containing phases in fly ashes from different combustion systems

Abstract: Abstract. The investigations of iron-containing phases existing in fl y ashes were performed using transmission Mössbauer spectrometry. The examined samples of fl y ashes were collected from different coal combustion systems, that is, stoker-fi red boiler in municipal heating plant and pulverized coal boiler in power plant. Several phases are identifi ed in the samples: iron oxides, paramagnetic aluminosilicate glass with Fe 3+ ions and Al 2 O 4 --type spinel with Fe 2+ ions. It was pointed out that proportion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…In both possible cases, G05 component describes the mineral of strongly defected structure, because of the very broad distribution of IS values (the variance value bigger than 0.4 mm/s). G06 component with considerably lower values of IS and QS comes presumably from paramagnetic Fe 3+ ions in amorphous (glassy) aluminosilicates (mullite-porcellanite, Al 6 Si 2 O 13 ), the presence of which in both fl y ashes and industrial dusts is widely reported in the literature [1,12,30]. The highest contribution of G05 component is stated for the sample COK1-P2 (coke dust collected in electrostatic precipitator), whereas G06 one dominates in the samples COK2-P3 and COK3-P7 (coke dusts collected by manual sweeping).…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…In both possible cases, G05 component describes the mineral of strongly defected structure, because of the very broad distribution of IS values (the variance value bigger than 0.4 mm/s). G06 component with considerably lower values of IS and QS comes presumably from paramagnetic Fe 3+ ions in amorphous (glassy) aluminosilicates (mullite-porcellanite, Al 6 Si 2 O 13 ), the presence of which in both fl y ashes and industrial dusts is widely reported in the literature [1,12,30]. The highest contribution of G05 component is stated for the sample COK1-P2 (coke dust collected in electrostatic precipitator), whereas G06 one dominates in the samples COK2-P3 and COK3-P7 (coke dusts collected by manual sweeping).…”
Section: Resultsmentioning
confidence: 90%
“…In comparison with the road dusts [11], the metallurgical dust and slurry contained signifi cantly less metallic iron. The investigated coke dusts revealed the similar abundance of glassy phase as fl y ashes from power plants and heat plants [12]. In general, the content of specifi c iron-bearing phases in the studied industrial dusts strongly depends on the place of collection of dusty material coming from different stages of blast furnace charge preparation process.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The fitting procedure offers a convolution of the Lorentzian baseline with Gaussian distributions of hyperfine parameters resulting in the final form as the Voigt profile. The PolMöss software and fitting method was efficiently applied in processing of the Mössbauer spectra of the environmental samples like highways and industrial dusts, fly ashes from power and heat plants as well as natural soils [12][13][14].…”
Section: Samples and Experimental Methodsmentioning
confidence: 99%
“…Unfortunately Mosgraf software, at present stage of development, offers fitting procedures only for the nanoparticles of the same size (or several discrete groups of different diameters). There is no options for continuous distribution of nanoparticle size, that is why at present work a PolMöss software (Szumiata et al [12][13][14]) has been utilized due to the hyperfine parameters distribution functionality (described in previous section). According to Eq.…”
Section: Theoretical Modelmentioning
confidence: 99%